Public Hospitals : Options for Reform through Public-Private Partnerships - Taylor, Rob; Blair, Simon (World Bank, Washington, DC, 2012)
As governments struggle with rising health care costs, public-private partnerships in constructing and managing public hospitals can provide innovative ways to control costs and improve service. Experience shows that such partnerships offer significant benefits as long as policymakers structure the transactions carefully and create sound regulatory arrangements to ensure universal access, quality care, and improvements in efficiency.